Comparative transcriptome profiling reveals a mechanism of Streptococcus agalactiae resistance to florfenicol. (May 2020) - Zhang, Ze; Li, Yuhui; Hu, Minqiang; Yu, Angen
Abstract: Florfenicol is widely used to control diseases in aquatic animals, and is used extensively to treat streptococcosis—caused by Streptococcus agalactiae —in the commercially important fish tilapia. There are known issues with the development of florfenicol resistance in Streptococcus agalactiae, but the underlying resistance mechanisms are not clear, a situation currently preventing optimal deployment of antibiotics. Here, we examined the induction of resistance by successively increasing the concentrations of florfenicol, and then used RNA-sequencing (RNA-Seq) to characterize changes in the transcriptomes of a florfenicol-resistant strain (H51-R) and a florfenicol-sensitive strain (H51–S). We obtained a total of 18, 418, 068 sequence reads in H51-R and 16, 070, 122 sequence reads in H51–S, from which a total of 1940 unigenes were assembled. In total, 376 unigenes were found to be differently expressed genes (DEGs). After florfenicol treatment, 181 genes were upregulated and 195 genes were downregulated. GO functional analysis of the DEGs indicated that the most strongly enriched GO terms included metabolic process (152 genes), catalytic activity (146), and binding (133), with terms including membrane, membrane part, and transporter activity also showing enrichment. KEGG pathway enrichment analysis highlighted that ribosomes were prominently involved in the transcriptional changes associated with florfenicol resistance. This study demonstrates that florfenicol treatment affects multiple biological functions of Streptococcus agalactiae, suggests that florfenicol resistance in Streptococcus agalactiae is closely related to the reduction of intracellular drug accumulation caused by ATP-binding cassette (ABC) transporters, and highlights the potential involvement of altered ribosomal function in florfenicol resistance. Highlights: We induced the development of GBS resistance by successively increasing the concentrations of FLO. We carried out FLO-resistant strain (H51-R) transcriptome profiling in comparison with a FLO-sensitive strain (H51–S). Our findings indicates the mechanisms maybe ribosome-mediated ABC transporters induced FLO resistance.